Makna-Cinta Menurut Victor Frankl Melawan Nihil-Hedonisme: Altruisme Menuju Kebahagiaan dalam Kehidupan Bermasyarakat - Satyawardhana, Fransiskus Antonius Dimas; Pitang, Simon Pedro (Jayapangus Press, 2024)
The focus of this study is Victor Frankl's philosophical reflection on meaning and love as a guideline for dealing with nihilism today. Nihilism in this modern era has now begun to invite many people in the world to live a meaningless life and just seek mere pleasure; nihil-hedonism. This understanding then leads humans to the abyss of true self-actuality; where humans cannot find themselves more valuable and valuable. The method used in this study is a literature study through reading from Victor Frankl's books. In addition, other supporting sources on the meaning and love of life are also taken to help explain the philosophical values of Victor Frankl's thought. This study is based on critical reading and critical analysis with philosophical reflection on the meaning of life and love in the perspective of Victor Frankl and other sources. The purpose of this study is none other than to understand how humans are entangled in nihil-hedonism, and how the solution of the philosophy of the meaning of life and love from Victor Frankl's thought can provide a way for a non-meaningful society today. Through this study, an understanding is obtained that in the midst of a world that offers a meaningless life, humans have the ability to achieve a valuable and worthwhile life through the search for meaning and love. Nihil-hedonism can be faced with the discovery of Meaning-Love in the human person. Furthermore, it will also be discovered how humans who have Meaning-Love become individuals characterized by altruism who walk together with society towards happiness in social life. The contribution of this study is to awaken the altruism attitude in human beings and create a meaningful life through the Meaning-Love that exists in them.